Kartu Skor Poedji Rochyati in the Indonesian Maternal Referral System - Sihotang, Jojor; Hidayatullah, Amiruddin (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS 1. This review focuses on maximizing the effectiveness of "Kartu Skor Poedji Rochyati" (KSPR) in Indonesia's maternal referral system.2. It addresses the lack of information about Indonesia's maternal referral system, offering valuable insights.3. Underlining the high rates of maternal and fetal deaths due to referral errors, the article stresses the urgency of understanding KSPR's function for high-risk pregnant women.   ABSTRACT Maternal Mortality Rate (MMR) represents fatalities during pregnancy, childbirth, and the postpartum period due to complications, not external factors. Timely detection is crucial for preventing maternal deaths, necessitating integrated planning. The "Kartu Skor Poedji Rochjati" (KSPR) emerges as a vital tool for identifying high-risk pregnancies, facilitating urgent referrals to mitigate complications and enhance healthcare. A literature review on maternal mortality, risk assessment tools, and KSPR effectiveness was conducted to address the issues. The findings are expected to highlight KSPR's pivotal role in identifying at-risk pregnant women, enabling prompt referrals, and reducing maternal mortality rates. The case studies and data analysis will enrich our understanding of the tool's impact on maternal healthcare. The apex of public health involves embracing health-conscious lifestyles, reflected in indicators like mortality and morbidity. Proactively identifying high-risk pregnancies using KSPR is a strategic step in averting maternal mortality. Leveraging KSPR allows early intervention, reducing complications and contributing to enhanced maternal health, aligning with the goal of minimizing mortality risks.